Neutrino pair annihilation above merger remnants: implications of a long-lived massive neutron star. (11th July 2017) - Perego, A; Yasin, H; Arcones, A
Abstract: Binary neutron star (BNS) mergers are plausible progenitor candidates for short gamma-ray bursts (GRBs); however, a detailed explanation of their central engine is still lacking. The annihilation of neutrino pairs has been proposed as one of the possible powering mechanisms. We present calculations of the energy and momentum deposition operated by neutrino pair annihilation above merger remnants. Starting from the results of a detailed, three-dimensional simulation of the aftermath of a BNS merger, we compute the deposition rates over a time scale comparable to the life time of the disk ( t ≈ 0.4 s), assuming a long-lived massive neutron star (MNS). We model neutrino emission using a spectral leakage scheme and compute the neutrino annihilation rates using a ray-tracing algorithm. We find that the presence of the MNS increases the energy deposition rate by a factor ∼2, mainly due to the annihilation of radiation coming from the MNS with radiation coming from the disk. We compute the impact of relativistic effects and discover that, despite the significant change to the local rate intensity, the volume-integrated results are only marginally decreased. The cumulative deposited energy, extrapolated to 1 s, is ≈ 2.2 × 10 49 erg . A comparison with the inferred short GRB energetics reveals that the deposited energy is compatible with a significant fraction of the observed bursts, if small jet opening angles ( ≲ 6 ° ) and long-lived MNSs are assumed, and if model uncertainties in the neutrino luminosities are taken into account. More intense neutrino luminosities (a factor 5–10 larger) are required to explain energetic short GRBs, in the case of larger jet opening angles.